Golf ball containing matte agent and method for producing same
The golf ball design incorporates a matte agent and a specific polyurethane paint formulation to achieve a non-glossy appearance and improved spin performance by maintaining a high static friction coefficient, addressing the issue of reduced spin due to surface roughness.
Patent Information
- Application Number
- JP2021102574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-21
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2041-06-21
AI Technical Summary
Golf balls with matte agents in their paint layers experience increased surface roughness, leading to slippery surfaces and reduced backspin during approach shots, resulting in insufficient spin performance.
A golf ball design featuring a coating layer with a matte agent, specifically silica with hydrophilic surface treatment, and a polyurethane paint formulation that includes a solvent with a boiling point of 130° C or higher, achieving an average roughness Ra of 0.35 or more and a static friction coefficient of 0.20 or more.
The solution provides a non-glossy appearance while enhancing spin performance during approach shots by maintaining a sufficient static friction coefficient, thus improving the golf ball's aerodynamic characteristics.
Smart Images

Figure 0007667699000002 
Figure 0007667699000003 
Figure 0007667699000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a golf ball containing a matting agent and a method for making the same. [Background technology]
[0002] In recent years, many matte-painted golf balls have been commercialized for the sake of a sense of luxury and visibility. This type of golf ball is generally produced by adding a matte agent to the paint film layer, which is the outermost layer of the golf ball, and creating irregularities on the surface of the golf ball to give it a matte appearance.
[0003] For example, JP 2020-000624 A describes a method for forming a coating layer, which is the outermost layer of a golf ball, having a BET specific surface area of 200 to 400 m 2 / g and an average primary particle size of 1.0 to 3.0 μm, thereby making the average roughness Ra of the coating layer surface 0.5 to 1.0. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-000624 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when a coating layer is formed using paint containing a matting agent, the surface roughness of the golf ball increases compared to a coating layer formed using paint that does not contain a matting agent, making the surface slippery and significantly reducing the amount of backspin on the golf ball during approach shots, resulting in the problem that a sufficient amount of spin cannot be obtained.
[0006] In view of the above problems, the present invention has an object to provide a golf ball which has a matte appearance due to a coating layer containing a matting agent and which also has excellent spin performance on approach shots, and a method for manufacturing the same. [Means for solving the problem]
[0007] In order to achieve the above object, one aspect of the present invention is a golf ball comprising a core, a cover located outside the core and having a plurality of dimples, and a coating layer located outside the cover, the coating layer containing a matting agent, the average surface roughness Ra of the coating layer being 0.35 or greater, and the static friction coefficient of the surface of the golf ball being 0.20 or greater.
[0008] The static friction coefficient may be 0.24 or greater.
[0009] The surface of the golf ball may have a surface energy of 40 dyn or greater.
[0010] The matting agent may be silica having a hydrophilic surface treatment.
[0011] The coating layer may have an edge ratio, which is a ratio of the thickness of the coating layer at the edge portion of the dimple to the thickness of the coating layer at the center portion of the dimple, of 70% or less.
[0012] The coating layer may include a urethane coating material, the urethane coating material may include a polyisocyanate as a curing agent, and the polyisocyanate may include both an adduct and an isocyanurate of hexamethylene diisocyanate.
[0013] In another aspect, the present invention is a method for manufacturing a golf ball, the method for manufacturing a golf ball including a step of forming a coating layer on a surface of a cover having a plurality of dimples, the coating layer being formed from a paint composition including a polyurethane paint, a matting agent, and a solvent having a boiling point of 130°C or higher, the average roughness Ra of the surface of the coating layer being 0.35 or greater, and the static friction coefficient of the surface of the golf ball being 0.20 or greater.
[0014] The solvent may be propylene glycol monomethyl ether acetate or methoxybutyl acetate. Effect of the Invention
[0015] Thus, according to the present invention, a coating layer containing a matting agent is formed on the surface of a cover having a plurality of dimples, and even if the average roughness Ra of the coating layer surface is 0.35 or more, the static friction coefficient of the surface of the golf ball is 0.20 or more, which gives the ball a matte appearance and also provides excellent spin performance on approach shots, and a method for manufacturing the same can be provided. [Brief description of the drawings]
[0016] [Figure 1] 1 is a cross-sectional view showing a schematic view of the periphery of a dimple of a golf ball according to the present invention. [Diagram 2] 1 is a graph showing the relationship between the static friction coefficient measured in the examples and the flight distance (carry) upon a driver shot. [Diagram 3] 1 is a graph showing the relationship between the static friction coefficient measured in an example and the spin rate during an approach shot. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of a golf ball and a method for manufacturing the same according to the present invention will be described with reference to the accompanying drawings.
[0018] The golf ball of this embodiment mainly comprises a core located at the center of the ball, a cover provided outside the core and having a plurality of dimples formed thereon, and a coating layer containing a matting agent provided outside the cover. In this embodiment, a golf ball having a two-layer structure of a core and a cover will be described, but the present invention is not limited thereto, and the golf ball may have an intermediate layer between the core and the cover, or may have a multi-layer core having two or more layers. Each component of the golf ball of this embodiment will be described.
[0019] The core can be mainly formed of a base rubber. As the base rubber, a wide variety of rubbers (thermosetting elastomers) can be used, including, but not limited to, polybutadiene rubber (BR), styrene butadiene rubber (SBR), natural rubber (NR), polyisoprene rubber (IR), polyurethane rubber (PU), butyl rubber (IIR), vinyl polybutadiene rubber (VBR), ethylene propylene rubber (EPDM), nitrile rubber (NBR), and silicone rubber. As the polybutadiene rubber (BR), for example, 1,2-polybutadiene, cis-1,4-polybutadiene, etc. can be used.
[0020] In addition to the base rubber as the main component, the core may optionally contain, for example, a co-crosslinking agent, a crosslinking agent, a filler, an antioxidant, an isomerizing agent, a mastication accelerator, sulfur, and an organic sulfur compound. Also, instead of the base rubber, a thermoplastic elastomer, an ionomer resin, or a mixture thereof may be used as the main component.
[0021] The core has a substantially spherical shape. The upper limit of the outer diameter of the core is preferably about 42 mm or less, more preferably about 41 mm or less, and even more preferably about 40 mm or less. The lower limit of the outer diameter of the core is preferably about 5 mm or more, more preferably about 15 mm or more, and most preferably about 25 mm or more. The core may be solid or hollow. The core may be a single layer, or may be a core consisting of multiple layers such as a center core and a surrounding layer.
[0022] The cover may be formed using, but is not limited to, a thermoplastic polyurethane, an ionomer resin, or a mixture thereof.
[0023] The structure of the thermoplastic polyurethane material is composed of a soft segment made of a polymer polyol (polymeric glycol) and a chain extender and a polyisocyanate that constitute a hard segment. Here, the polymer polyol used as the raw material is not particularly limited, but in the present invention, polyester polyols and polyether polyols are preferred. Specific examples of polyester polyols include adipate polyols such as polyethylene adipate glycol, polypropylene adipate glycol, polybutadiene adipate glycol, and polyhexamethylene adipate glycol, and lactone polyols such as polycaprolactone polyol. Examples of polyether polyols include poly(ethylene glycol), poly(propylene glycol), and poly(tetramethylene glycol).
[0024] The chain extender is not particularly limited, but in the present invention, a low molecular weight compound having two or more active hydrogen atoms in the molecule capable of reacting with an isocyanate group and a molecular weight of 2,000 or less can be used, and among these, an aliphatic diol having 2 to 12 carbon atoms is preferred. Specific examples include 1,4-butylene glycol, 1,2-ethylene glycol, 1,3-butanediol, 1,6-hexanediol, 2,2-dimethyl-1,3-propanediol, and the like, and among these, 1,4-butylene glycol is particularly preferred.
[0025] The polyisocyanate compound is not particularly limited, but in the present invention, for example, one or more compounds selected from the group consisting of 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, naphthylene 1,5-diisocyanate, tetramethylxylene diisocyanate, hydrogenated xylylene diisocyanate, dicyclohexylmethane diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, trimethylhexamethylene diisocyanate, and dimer acid diisocyanate can be used. However, depending on the type of isocyanate, it may be difficult to control the crosslinking reaction during injection molding. Therefore, in the present invention, from the viewpoint of the balance between stability during production and the physical properties exhibited, the aromatic diisocyanate 4,4'-diphenylmethane diisocyanate is preferred.
[0026] The ionomer resin may be, but is not limited to, one having the following component (a) and / or component (b) as the base resin. Optionally, the following component (c) may be added to this base resin. The component (a) is an olefin-unsaturated carboxylic acid-unsaturated carboxylic acid ester ternary random copolymer and / or a metal salt thereof, the component (b) is an olefin-unsaturated carboxylic acid binary random copolymer and / or a metal salt thereof, and the component (c) is a thermoplastic block copolymer having a polyolefin crystalline block and a polyethylene / butylene random copolymer.
[0027] In addition to the main component of the thermoplastic polyurethane or ionomer resin, the resin for the cover may contain a thermoplastic resin or elastomer other than the thermoplastic polyurethane. Specifically, one or more of polyester elastomers, polyamide elastomers, ionomer resins, styrene block elastomers, hydrogenated styrene butadiene rubber, styrene-ethylene / butylene-ethylene block copolymers or modified products thereof, ethylene-ethylene / butylene-ethylene block copolymers or modified products thereof, styrene-ethylene / butylene-styrene block copolymers or modified products thereof, ABS resins, polyacetals, polyethylene, and nylon resins may be used. In particular, polyester elastomers, polyamide elastomers, and polyacetals are preferably used because they maintain good productivity while improving resilience and abrasion resistance through reaction with isocyanate groups. When the above components are blended, the blending amount is appropriately selected depending on the adjustment of the hardness of the cover material, the improvement of the resilience, the improvement of the fluidity, the improvement of the adhesion, etc., and is not particularly limited, but is preferably 5 parts by mass or more per 100 parts by mass of the thermoplastic polyurethane component. In addition, the upper limit of the blending amount is also not particularly limited, but is preferably 100 parts by mass or less, more preferably 75 parts by mass or less, and even more preferably 50 parts by mass or less per 100 parts by mass of the thermoplastic polyurethane component. In addition, polyisocyanate compounds, fatty acids or derivatives thereof, basic inorganic metal compounds, fillers, etc. may be added.
[0028] The thickness of the cover is not limited to these values, but the lower limit is preferably 0.2 mm or more, and more preferably 0.4 mm or more, and the upper limit is preferably 4 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less.
[0029] The material hardness of the cover is not limited to, but the upper limit is preferably about 60 or less, more preferably about 55 or less, and even more preferably about 50 or less, in Shore D. The lower limit is preferably about 35 or more, and more preferably about 40 or more, in Shore D. The material hardness of the cover is measured in accordance with the ASTM D2240-95 standard after the resin material for the cover is molded into a sheet having a thickness of 2 mm and allowed to stand for at least two weeks.
[0030] The coating layer is formed from a paint containing a matting agent. The paint is not particularly limited, but for example, a polyurethane paint is preferably used, and in particular, a two-component curing polyurethane paint is more preferably used.
[0031] Examples of the matting agent include silica-based, melamine-based, and acrylic-based agents. Specific examples include silica, polymethyl methacrylate, polybutyl methacrylate, polystyrene, and polybutyl acrylate. Either organic or inorganic matting agents may be used, but silica is particularly preferred.
[0032] When such a matting agent is contained in the paint layer, the surface of the golf ball becomes uneven, which results in the golf ball surface having a dull appearance. As an index, if the surface roughness Ra of the golf ball surface is 0.35 or more, an excellent matte appearance can be imparted to the golf ball surface. The surface roughness Ra means the arithmetic mean roughness according to JIS B0601 (1994). However, according to the present inventor, when a coating layer is formed with a paint containing such a matting agent, the static friction coefficient of the golf ball surface is significantly reduced to less than 0.20 compared to a coating layer formed with a paint not containing the matting agent, and this has been found to significantly reduce the amount of backspin of the golf ball during an approach shot. That is, the present invention is such that the static friction coefficient of the golf ball surface can be 0.20 or more even if the surface roughness Ra of the golf ball surface is 0.35 or more by adding a matting agent to the paint layer.
[0033] In this embodiment, for example, by using hydrophilically surface-treated silica as the matting agent, the static friction coefficient of the golf ball surface can be made 0.20 or more even if the surface roughness Ra of the golf ball surface is 0.35 or more. The hydrophilically surface-treated silica is partially exposed from the golf ball surface, forming irregularities on the golf ball surface, and the hydrophilic surface can improve the static friction coefficient of the golf ball surface.
[0034] The static friction coefficient of the golf ball surface is preferably 0.24 or more. The method for measuring the static friction coefficient will be described in detail in the Examples. The upper limit of the static friction coefficient is not particularly limited, but is preferably 0.40 or less, more preferably 0.35 or less, and even more preferably 0.30 or less.
[0035] Examples of silica that has been subjected to hydrophilic surface treatment include SS-50B, SS-170X, SS-178B, and SS-50A, which are available under the trade name Nipsil (manufactured by Tosoh Corporation). On the other hand, the present invention is not limited to using silica that has been subjected to hydrophilic surface treatment as a matting agent, and silica that has not been subjected to hydrophilic surface treatment may be used. Examples of silica that has not been subjected to hydrophilic surface treatment include E-200A, E-220A, K-500, E-1009, E-1011, E-1030, E-150J, E-170, E-200, and E-220, which are available under the trade name Nipsil (manufactured by Tosoh Corporation). For example, when it is necessary to use a matting agent with high dispersibility, silica that has not been subjected to hydrophilic surface treatment is preferred. Both silica that has been subjected to hydrophilic surface treatment and silica that has not been subjected to hydrophilic surface treatment may be used in combination.
[0036] The amount of the matting agent is not particularly limited as long as the surface roughness Ra of the golf ball surface is 0.35 or more, but for example, it is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 7 parts by mass or more, per 100 parts by mass of the main component (total amount of resin component and solvent) of the coating composition of the coating layer. The upper limit of the amount of the matting agent is, for example, preferably 10 parts by mass or less, since if it is too high, the viscosity of the coating composition increases and the coating workability tends to deteriorate.
[0037] In addition, in this embodiment, by using a specified polyurethane paint, the static friction coefficient of the golf ball surface can be made 0.20 or more, even if the surface roughness Ra of the golf ball surface is made 0.35 or more by using a matting agent.
[0038] First, a polyurethane coating material that is commonly used will be described. A two-component curing polyurethane coating material is composed of a polyol as a main agent and a polyisocyanate as a curing agent. The polyol is not limited to this, but it is preferable to use a polycarbonate polyol or a polyester polyol, and two kinds of polyester polyols, that is, a polyester polyol (A) and a polyester polyol (B), may be used. When using these two kinds of polyester polyols, the weight average molecular weights (Mw) are different, and it is preferable that the weight average molecular weight (Mw) of the (A) component is 20,000 to 30,000 and the weight average molecular weight (Mw) of the (B) component is 800 to 1,500. The weight average molecular weight (Mw) of the (A) component is more preferably 22,000 to 29,000, and further preferably 23,000 to 28,000. The weight average molecular weight (Mw) of the component (B) is more preferably from 900 to 1,200, and even more preferably from 1,000 to 1,100.
[0039] The polyester polyol is obtained by polycondensation of a polyol and a polybasic acid. Examples of the polyol include diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, hexylene glycol, dimethylolheptane, polyethylene glycol, and polypropylene glycol, triols, tetraols, and polyols having an alicyclic structure. Examples of polybasic acids include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, azelaic acid, and dimer acid, aliphatic unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, and citraconic acid, aromatic polyvalent carboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, and pyromellitic acid, dicarboxylic acids having an alicyclic structure such as tetrahydrophthalic acid, hexahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and endomethylenetetrahydrophthalic acid, and tris-2-carboxyethyl isocyanurate. In particular, polyester polyols having a cyclic structure introduced into the resin skeleton can be used as the polyester polyol of component (A), and examples thereof include polyester polyols obtained by polycondensation of a polyol having an alicyclic structure such as cyclohexanedimethanol with a polybasic acid, or polycondensation of a polyol having an alicyclic structure with a diol or triol with a polybasic acid. On the other hand, as the polyester polyol of component (B), a polyester polyol having a multi-branched structure can be used, and an example thereof includes polyester polyols having a branched structure such as "NIPPOLAN 800" manufactured by Tosoh Corporation.
[0040] In addition, when the above-mentioned polyester polyol is used, the weight average molecular weight (Mw) of the entire base material is preferably 13,000 to 23,000, more preferably 15,000 to 22,000. In addition, the number average molecular weight (Mn) of the entire base material is preferably 1,100 to 2,000, more preferably 1,300 to 1,850. If these average molecular weights (Mw and Mn) deviate from the above ranges, the abrasion resistance of the coating layer may decrease. The weight average molecular weight (Mw) and the number average molecular weight (Mn) are measured values (polystyrene equivalent values) by gel permeation chromatography (hereinafter abbreviated as GPC) measurement by differential refractometer detection. In the case where two types of polyester polyols are used, the Mw and Mn of the entire base material are also within the above-mentioned ranges.
[0041] The blending amounts of the above two types of polyester polyols (A) and (B) are not particularly limited, but it is preferable that the blending amount of the (A) component is 20 to 30 mass % based on the total amount of the base material including the solvent, and the blending amount of the (B) component is 2 to 18 mass % based on the total amount of the base material.
[0042] The polyisocyanate is not particularly limited, but may be a commonly used aromatic, aliphatic, alicyclic, or other polyisocyanate, specifically, tolylene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), lysine diisocyanate, isophorone diisocyanate, 1,4-cyclohexylene diisocyanate, naphthalene diisocyanate, trimethylhexamethylene diisocyanate, dicyclohexylmethane diisocyanate, 1-isocyanato-3,3,5-trimethyl-4-isocyanatomethylcyclohexane, etc. These may be used alone or in combination.
[0043] Examples of the modified hexamethylene diisocyanate (HDI) include polyester modified HDI and urethane modified HDI. Examples of the derivatives of HDI include isocyanurate (nurate), biuret, and adduct of HDI. The adduct refers to an adduct of diisocyanate and trimethylolpropane. The nurate refers to a trimer of diisocyanate. In the present embodiment, the static friction coefficient of the golf ball surface can be increased to 0.20 or more by using two types of HDI, an adduct having excellent flexibility and a nurate having relatively high toughness, in combination, and thus high spin performance can be obtained during approach shots.
[0044] Since the static friction coefficient of the coating layer increases with an increase in the amount of the adduct, the mixing ratio of the isocyanurate to the adduct (isocyanurate / adduct) is preferably 90 / 10 or more, more preferably 86 / 14 or more, by mass ratio. On the other hand, if the amount of the adduct is too large, the coating layer becomes easily soiled, so this mixing ratio is preferably 40 / 60 or less, more preferably 50 / 50 or less.
[0045] Examples of isocyanurate HDIs include trade names Coronate 2357 (manufactured by Tosoh Corporation), Sumidur N3300 (manufactured by Sumika Covestro Urethanes), Duranate TPA-100 (manufactured by Asahi Kasei Corporation), Takenate D170N, Takenate D177N (all manufactured by Mitsui Chemicals), and Burnock DN-980 (manufactured by DIC Corporation). Examples of adduct HDIs include trade names Coronate HL (manufactured by Tosoh Corporation), Takenate D160N (manufactured by Mitsui Chemicals), Duranate E402-80B, Duranate E405-70B (all manufactured by Asahi Kasei Corporation), Burnock DN-955, and Burnock DN-955S (all manufactured by DIC Corporation).
[0046] In the urethane coating material consisting of polyol and polyisocyanate as main components, the molar ratio (NCO group / OH group) of the hydroxyl group (OH group) of the polyol to the isocyanate group (NCO group) of the polyisocyanate is preferably 0.6 or more as a lower limit, more preferably 0.65 or more. The upper limit of this molar ratio is preferably 1.5 or less, more preferably 1.0 or less, and even more preferably 0.9 or less. If this molar ratio is below the above lower limit, unreacted hydroxyl groups may remain, which may deteriorate the performance and water resistance of the coating layer. On the other hand, if the molar ratio exceeds the above upper limit, the isocyanate group becomes excessive, and urea groups (brittle) are generated by reaction with moisture, which may result in a deterioration in the performance of the coating layer.
[0047] As the curing catalyst (organometallic compound) that promotes the reaction between polyol and polyisocyanate, an amine catalyst or an organometallic catalyst can be used. As this organometallic compound, metal soaps such as aluminum, nickel, zinc, tin, etc., which have traditionally been blended as curing agents in two-component curing urethane paints, can be suitably used.
[0048] The coating layer may further contain known additives as necessary. Specifically, the coating layer may contain appropriate amounts of a water repellent additive, a thickener, an ultraviolet absorber, a fluorescent whitening agent, a pigment, etc.
[0049] In this embodiment, the content of the water-repellent additive in the coating layer is reduced from the usual amount, and the surface energy of the coating layer (golf ball surface) is increased, so that even if the coating layer contains a matting agent, the static friction coefficient of the golf ball surface can be increased to 0.20 or more, and high spin performance can be obtained during approach shots. The higher the surface energy, the better the spin performance of the golf ball. The surface energy increases when silica with a hydrophilic surface treatment is used as the matting agent, but there is almost no increase when silica without a hydrophilic surface treatment is used. Therefore, when silica without a hydrophilic surface treatment is used, the static friction coefficient of the golf ball surface can be increased to 0.20 or more by increasing the surface energy by the content of the water-repellent additive.
[0050] The surface energy of the golf ball surface is preferably 34 dyn or more, more preferably 40 dyn or more, and even more preferably 44 dyn or more. The upper limit of the surface energy is preferably 50 dyn or less, more preferably 48 dyn or less, because if the surface energy is too high, the golf ball surface becomes easily soiled. The surface energy can be measured by a method using multiple dyne pens in increments of 2 mN / m. The specific content of the water-repellent additive varies depending on the type of water-repellent additive, but the lower limit is preferably 0.02 mass% or more, more preferably 0.05 mass% or more, and the upper limit is preferably 1.0 mass% or less, more preferably 0.7 mass% or less, based on 100 parts by mass of the main agent (total amount of resin component and solvent).
[0051] As the water-repellent additive, for example, silicone resin, silicone oil, silicone rubber, fluorine-based surfactant, or a combination thereof can be used. As the silicone resin, but not limited thereto, silicone-modified acrylate can be used. Silicone-modified acrylate is a surface conditioner in which an acrylic structure and a silicone structure are incorporated in one molecule. Unlike ordinary polyrotaxane-based silicone, the silicone-modified acrylate has a polysiloxane chain attached to the acrylic skeleton, so that even if the amount of the silicone-modified acrylate is increased, it is difficult to slip, and water repellency can be increased. As the silicone-modified acrylate, for example, there are trade names BYK3550 and BYK3700 (both manufactured by BYK-Chemie). As the silicone oil, for example, methyl hydrogen silicone oil, dimethyl silicone oil, etc. can be mentioned.
[0052] The thickness of the coating layer is usually different between the center of the dimple on the cover and the edge of the dimple. Therefore, an index called an edge ratio is used as the ratio of the coating layer thickness at the edge of the dimple to the coating layer thickness at the center of the dimple. The closer the edge ratio is to 100%, the more uniform the coating layer thickness is. In this embodiment, since a lower edge ratio can improve the distance performance in driver shots, the edge ratio is preferably 70% or less, and more preferably 60% or less.
[0053] On the other hand, if the edge ratio is too low, the coating layer at the edge portion becomes thin, the impact durability decreases, and the coating layer becomes easily peeled off, so the lower limit of the edge ratio is preferably 40% or more, more preferably 50% or more. More specifically, from the viewpoint of scratch resistance and peeling resistance, the coating layer at the edge portion has a thickness of, for example, preferably 5 μm or more, more preferably 7 μm or more. On the other hand, if the coating layer is too thick, it affects the aerodynamic characteristics of the golf ball, so the upper limit is preferably 20 μm or less, more preferably 15 μm or less.
[0054] Next, a method for manufacturing the golf ball of the present embodiment will be described. The method includes a step of forming a coating layer on the surface of a cover having a plurality of dimples.
[0055] The coating composition used to form the coating layer contains the above-mentioned polyurethane coating, a matting agent, and additives such as a water-repellent additive. The coating composition further contains a solvent for the main agent, polyol, and a hardener, polyisocyanate, in addition to the polyurethane coating. The components other than the solvent have already been described, so they will not be described here.
[0056] Usually, when a coating layer is formed on the recessed surface of a dimple, the thickness of the coating becomes thinner at the edge portion, which is the shallow portion of the recess, and thicker at the center portion, which is the deep portion of the recess. That is, the above edge ratio is lower than 100%, but in this embodiment, as described above, a lower edge ratio can improve the flight distance performance. In order to form such a coating layer with a low edge ratio, it is preferable to use a solvent with a boiling point of 130°C or more. The higher the boiling point, the easier it is to level (smooth) the coating film, and the easier it is to sag. It is more preferable to use a solvent with a boiling point of 150°C or more. Examples of such solvents include propylene glycol monomethyl ether acetate (boiling point: 148°C) and methoxybutyl acetate (boiling point: 171°C).
[0057] The present invention is not limited to such solvents, and a solvent having a boiling point of 130°C or more may be used in combination with a solvent having a boiling point of less than 130°C, or only a solvent having a boiling point of less than 130°C may be used. Examples of solvents having a boiling point of less than 130°C include ester solvents such as methyl acetate (57°C), ethyl acetate (77°C), and butyl acetate (126°C), hydrocarbon solvents such as normal hexane (68°C), cyclohexane (80°C), and benzene (80°C), and ketone solvents such as acetone (56°C) and methyl ethyl ketone (79°C) (boiling points in parentheses). The amount of the solvent having a boiling point of 130°C or more is preferably 5% by mass or more, more preferably 10% by mass or more, based on the total mass of the coating composition. The total mass of the coating composition is the sum of the total mass of the base agent including the solvent and the total mass of the curing agent including the solvent.
[0058] The method for forming the coating layer is not particularly limited, and any known method for applying a golf ball paint to the cover surface can be used, such as spray coating or electrostatic coating, etc. In this way, the coating layer can be formed on the cover surface.
[0059] After the coating layer is formed, a step of drying the coating layer may be performed. The drying conditions may be the same as known conditions for drying urethane paint, and in this embodiment, for example, the drying temperature may be about 40° C. or higher, particularly 40 to 60° C., and the drying time may be 20 to 90 minutes, particularly 40 to 50 minutes.
[0060] This allows the formation of a coating layer having an average surface roughness Ra of 0.35 or more, and allows the manufacture of a golf ball having a surface static friction coefficient of 0.20 or more. The method for manufacturing a golf ball according to the present embodiment may further include the steps of forming a core and forming a cover having a plurality of dimples on the outside of the core. These steps will now be described.
[0061] The core can be molded by a known method for molding a golf ball core. For example, but not limited to, the material containing the base rubber described above can be kneaded in a kneading machine, and then the kneaded mixture can be pressure-vulcanized and molded in a round mold to obtain a core having multiple layers. In addition, the core can be molded by a known method for molding a multi-layered solid core. For example, the center core can be obtained by kneading the material in a kneading machine and pressure-vulcanizing and molding the kneaded mixture in a round mold, and then, as the surrounding layer, the material is kneaded in a kneading machine, and the kneaded mixture is molded into a sheet, and the sheet is used to cover the center core, and then the sheet is pressure-vulcanized and molded in a round mold to obtain a multi-layered core.
[0062] The method for forming the cover can be a known molding method for a golf ball cover. For example, but not limited to, the core can be placed in a mold and the resin composition for the cover can be injection molded to form the cover so as to cover the core. The mold for molding the cover has a plurality of protrusions for forming dimples on the cover surface. The size, shape, number, etc. of the dimples formed on the cover surface can be appropriately designed according to the desired aerodynamic characteristics of the golf ball. EXAMPLES
[0063] Examples and comparative examples of the present invention will be described below.
[0064] In producing the golf balls of the Examples and Comparative Examples, the coating layer of the golf ball was produced using the paint formulation shown in Table 1. The formulation in Table 1 is expressed in parts by mass. The coating layer thickness, surface roughness, static friction coefficient, and surface energy of the produced golf balls were measured, and the flying distance on a driver shot and the spin rate on an approach shot were also measured.
[0065] In the paint formulation shown in Table 1, a polyester polyol with a weight average molecular weight (Mw) of 28,000 was used as the main polyol (solid content). This was synthesized by the following method. 140 parts by mass of trimethylolpropane, 95 parts by mass of ethylene glycol, 157 parts by mass of adipic acid, and 58 parts by mass of 1,4-cyclohexanedimethanol were charged into a reaction apparatus equipped with a reflux condenser, a dropping funnel, a gas introduction tube, and a thermometer, and the temperature was raised to 200 to 240°C while stirring, and the mixture was heated (reacted) for 5 hours. After that, a polyester polyol with an acid value of 4, a hydroxyl value of 170, and a weight average molecular weight (Mw) of 28,000 was obtained.
[0066] The main solvents used were ethyl acetate (boiling point: 77°C), butyl acetate (boiling point: 126°C), propylene glycol monomethyl ether acetate (abbreviation: PGMEA) (boiling point: 148°C), and methoxybutyl acetate (abbreviation: MBA) (boiling point: 171°C).
[0067] The matting agent used was the silica "Finesil X-35" manufactured by Maruo Calcium Co., Ltd. (average primary particle size: 2.4 μm, BET specific surface area: 262 m 2 The coating was performed using a 100% acrylic acid-modified silica "SS-50A" manufactured by Tosoh Corporation (matt agent A) and a 100% acrylic acid-modified silica "SS-50A" manufactured by Tosoh Corporation (matt agent B). The additive used was silicone modified acrylate "BYK3700" manufactured by BYK-Chemie.
[0068] In the paint formulation shown in Table 1, the isocyanate (solid content) used as the curing agent was Asahi Kasei's hexamethylene diisocyanate (HDI) isocyanurate "Duranate TPA-100" (NCO content 23.1%, non-volatile content 100%) and Asahi Kasei's HDI adduct "Duranate E402-80B" (NCO content 7.6%, non-volatile content 80%). Butyl acetate (boiling point: 126°C) was used as the curing agent solvent.
[0069] Then, a paint in which the base agent and the curing agent were mixed in the blending ratio shown in Table 1 was spray-painted onto the cover to form a coating layer, thereby producing the golf balls of Examples 1 to 6 and Comparative Examples 1 and 2. The blending ratios of the core and the cover were all the same in the examples and comparative examples.
[0070] [Table 1]
[0071] [Method of measuring film thickness] The thicknesses of the coating film at the center and edge of the dimple in Table 1 were calculated by the following measurement method. First, 1 to 5 lines were drawn vertically at equal intervals on the cross section of the dimple 12 of the cover 10 shown in FIG. 1, and the lines were named No. 1, No. 2, No. 3, No. 4, and No. 5 in order from the edge E of the dimple to the opposite edge E', and the thickness of the coating film 20 on each line was measured. The thickness was measured by cutting the golf ball and measuring the thickness of the cross section at each position using a microscope. The average value of the thicknesses at No. 1 and No. 5 was taken as the thickness of the edge of the dimple, and the average value of the thicknesses at No. 2, No. 3, and No. 4 was taken as the thickness of the center of the dimple.
[0072] Then, the edge ratio, which is the ratio of the film thickness at the edge portion to the film thickness at the center portion of the dimple, was calculated by the following formula. Edge ratio [%] = (thickness of edge part) / (thickness of center part) × 100 The obtained film thicknesses of the central portion and edge portion, and the edge ratio are shown in Table 1.
[0073] [Surface roughness Ra] The surface roughness Ra of the golf ball surface (coating surface) of each example was measured using a Mitutoyo surface roughness tester "SV-C3000." The surface roughness Ra is the arithmetic mean roughness defined in JIS B0601 (1994). The results are shown in Table 1.
[0074] [Glossiness] The gloss of the golf ball surface (coating) was evaluated as follows. Using BYK's "micro-TRI-gloss," gloss was measured at incidence angles of 20° / 60° / 85°. For the gloss values at each measurement angle, if the value was 5.0 or less at an incidence angle of 20°, 20.0 or less at an incidence angle of 60°, or 40.0 or less at an incidence angle of 85°, the gloss was evaluated as being sufficiently suppressed and "none," and otherwise, it was evaluated as having gloss and being "present." The results are shown in Table 1.
[0075] [Static friction coefficient] The golf ball of each example was placed on a face plate (stainless steel), and a load was placed on the golf ball (normal force: 3.5N) using a testing machine "Tensilon RTG1310" manufactured by A&D Co., Ltd., and the golf ball was moved at a temperature of 23°C and a pulling speed of 50mm / min to measure the friction force (unit: N). The static friction coefficient μ was then calculated using the following formula. F is the friction force, and N is the normal force. The results are shown in Table 1. μ=F / N
[0076] [Surface Energy] Using a test pen (dyne pen) manufactured by MISHIMA, eight types of test pens with surface energies of 30 to 44 mN / m in 2 mN / m increments were used. A line was drawn on the surface (coating layer) of the golf ball with the test pen, and ink was applied in the line. As a result, if the ink applied to the ball surface did not turn into droplets and remained on the surface for more than two seconds, it was determined that the surface energy of the test pen was retained on the coating layer. The surface energy of the coating layer of each example was identified by using a test pen with each surface energy. The results are shown in Table 1.
[0077] [Spin amount, elevation angle, and distance on driver shots] A club was attached to a golf hitting robot, and the amount of backspin, elevation angle, and flight distance (carry) were measured when the ball was hit at a head speed of 45 m / s. The club used was a Bridgestone Sports driver "JGR (2016 model) loft angle 9.5°." The spin amount, elevation angle, and flight distance obtained are shown in Table 1. The relationship between the static friction coefficient and flight distance is shown in Figure 2.
[0078] [Spin rate on approach shots] A club was attached to a golf hitting robot, and the amount of backspin was measured and evaluated when hitting the ball at a head speed of 20 m / s. The club used was a sand wedge (SW) "TourB XW-1 SW" manufactured by Bridgestone Sports Co., Ltd. A spin amount of 4600 rpm or more was evaluated as "◎", 4400 rpm or more was evaluated as "○", and anything less than that was evaluated as "×". The obtained spin amount and the evaluation results are shown in Table 1. The relationship between the static friction coefficient and spin amount is shown in Figure 3.
[0079] As shown in Table 1, the golf ball of Comparative Example 1, in which a coating was formed using a matting agent without conventional surface treatment, had a dull, matte appearance compared to the golf ball of Comparative Example 2, in which a coating layer was formed without using a matting agent. However, the static friction coefficient was significantly reduced from 0.28 to 0.19, the spin rate on approach shots was significantly reduced, and the flight distance on driver shots was also reduced.
[0080] On the other hand, the golf balls of Examples 1 and 2, in which a matte agent with a hydrophilic surface was used and a coating layer was formed using a high-boiling point solvent as the main solvent, exhibited a matte appearance without any gloss, and the static friction coefficient improved to 0.26, a value close to that of Comparative Example 2, and the spin rate on approach shots and the flight distance on driver shots increased to almost the same level as Comparative Example 2.
[0081] The golf ball of Example 3, in which a coating layer was formed using a matte agent with a hydrophilic surface and a solvent with the same composition as in Comparative Example 1, exhibited a matte appearance without gloss, and the static friction coefficient was improved to 0.26, a value close to that of Comparative Example 2, and the spin rate on approach shots was also increased to almost the same level as in Comparative Example 2.
[0082] The golf ball of Example 4, which was formed by using the same amount of a matte agent with a hydrophilic surface treatment and a matte agent without a conventional surface treatment, and using the same solvent composition as in Comparative Example 1 to form a coating layer, exhibited a matte appearance without gloss and also improved static friction to 0.23. The spin rate on approach shots was increased compared to Comparative Example 1.
[0083] The golf ball of Example 5, which uses a matte agent without hydrophilic surface treatment as in Comparative Example 1, but reduces the content of the water-repellent additive silicone modified acrylate to one-tenth of that in Comparative Example 1 to form a coating layer, exhibits a matte appearance without gloss, has a high surface energy of 40 dyn, and has an improved static friction of 0.22. The spin rate during approach shots was higher than that of Comparative Example 1.
[0084] The golf ball of Example 6, which used a matte agent without hydrophilic surface treatment as in Comparative Example 1, but used a mixture of HDI in the adduct form as well as HDI in the isocyanurate form as a hardener to form a coating layer, exhibited a matte appearance without gloss and also had an improved static friction of 0.21. The spin rate during approach shots was higher than that of Comparative Example 1.
[0085] As shown in Fig. 3, from the results of Examples 1 to 6 and Comparative Examples 1 and 2, the higher the static friction coefficient of the golf ball surface, the more the spin rate during approach shots increased. It was found that a sufficient spin rate during approach shots can be obtained by setting the static friction coefficient of the golf ball surface to 0.20 or more.
[0086] In addition, as shown in FIG. 2, the results of Examples 1 to 6 and Comparative Examples 1 and 2 show that the higher the static friction coefficient of the golf ball surface, the longer the flight distance during driver shots. This tendency is also seen when excluding the results of Examples 1 and 2, in which the edge ratio was lowered to increase the flight distance. It is presumed that the reason for such results is that the increased coefficient of friction between the ball and the club results in a lower spin rate during driver shots, and thus increases the flight distance. Thus, it was found that the flight distance during driver shots can be improved by increasing the static friction coefficient of the golf ball surface. [Explanation of symbols]
[0087] 10. Cover 12 Dimples 20 Coating Layer
Claims
1. A golf ball comprising a core, a cover positioned outside the core and having a plurality of dimples, and a coating layer positioned outside the cover, The coating layer contains a matting agent, the coating layer has a surface average roughness Ra of 0.35 or more, the static friction coefficient of the surface of the golf ball is 0.20 or more, and the surface energy of the surface of the golf ball is 40×10 −5 N (40 dyn) or more.
2. 2. The golf ball according to claim 1, wherein the static friction coefficient is 0.24 or greater.
3. 3. The golf ball according to claim 1, wherein the matting agent is silica having a hydrophilic surface.
4. 4. The golf ball according to claim 1, wherein an edge ratio, which is a ratio of the thickness of the coating layer at the edge portion of the dimple to the thickness of the coating layer at the center portion of the dimple, is 70% or less.
5. 5. The golf ball according to claim 1, wherein the coating layer contains a urethane paint, the urethane paint contains a polyisocyanate as a curing agent, and the polyisocyanate contains both an adduct and an isocyanurate of hexamethylene diisocyanate.
6. 1. A method for manufacturing a golf ball, comprising the steps of: forming a coating layer on a surface of a cover having a plurality of dimples; The coating layer is formed by a coating composition containing a polyurethane coating, a matting agent, and a solvent having a boiling point of 130° C. or higher; The method for producing a golf ball, wherein the coating layer has a surface average roughness Ra of 0.35 or more and a static friction coefficient of the surface of the golf ball is 0.20 or more.
7. 7. The method for producing a golf ball according to claim 6, wherein the solvent is propylene glycol monomethyl ether acetate or methoxybutyl acetate.
Citation Information
Patent Citations
Golf ball
JP2003052858A
Golf ball
JP2005224293A
Golf ball
JP2019010191A
Golf ball
JP2020000624A